(3QjGV GdhQO Edi eG EfJgi Edjg gPG GdLhgQ GdaQOs - (3GdWGdH GHf GdMGL , eMeO GdWGdH Hf MeOhf Hf YHO GdQMef GdMGL GdSdej GdHNGQj GdaGSj,J (B1273 (3g` s
(3ChdgG (B:s
(3Ef NjQ eG SWQJg GdCbdGe MeO Gddg gPG heP fjWJ Yfi GdJeGFe GYJfjJ HGdaMU Yf GdOQ Gdecfhf ef fSH hBHGA CHj GdajV MeOhf s
(3BNQgG (B:s
(3bO QTMhc dCeQ dh aWfJ dg aCQHC HfaSc Cf JQYi Gdged s
(3hgh ai fSH hBHGA hCHi GdajV MeOhf Hf YHO GdQMef Hf MeOhf Hf YHO GdQMef Hf GdMGL GdSdei GdeQOGSi GdaGSi GdeJhai SfI (B1232(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B171 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B95s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B220 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B(111(3O(B) s
Keywords: (3GdJGQjNs